A Full-Duplex Relay Based Hybrid Transmission Mechanism for the MIMO-Capable Cooperative Intelligent Transport System. (19th May 2015) - Oh, Hayoung; Ahn, Sanghyun
Abstract : The goal of the cooperative intelligent transport system (C-ITS) is to provide a vehicular communication system that can enable quick, cost-effective means to distribute data in order to ensure safety, traffic efficiency, driver comfort, and so forth. The vehicular communication for C-ITS is composed of vehicle-to-infrastructure (V2I) and vehicle-to-vehicle (V2V) communications. In V2I, signals from roadside units (RSUs) often have to propagate through large buildings in urban areas, which can cause signal loss due to shadowing effects. V2V can provide video streaming capabilities to enable enhanced C-ITS services, but communication among vehicles may suffer from network congestion. Therefore, we propose a hybrid transmission mechanism in this paper based on full-duplex relay vehicles for MIMO-capable C-ITS. We adopt the use of full-duplex relay vehicles to enhance the reliability of seamless video stream transmission in V2I. For congestion resolution in V2V communications, the MIMO transmission mode is adapted according to the traffic situation and an extra detour path is used to satisfy various QoS requirements of multipriority video data. Simulations are also carried out to show that our mechanism improves the network throughput of MIMO-capable C-ITS with video streaming capability.